Reciprocal Management in MAPALUS As A Model of Community Economic Empowerment in Southeast Minahasa, North Sulawesi - Treesje Imran (AIBPM Publisher, 2018)
Mapalus is a Minahasan local wisdom-based system of cooperative work through reciprocal management system in which each member of the community has equal an opportunity or turn. This empowerment model has been implemented generation after generation. The Minahasan philosophy of Sitou Tumou Tumou Tou (meaning “Humans live to let other humans live”) is the ethical foundation of mapalus. There are many types of mapalus, such as agricultural mapalus, housebuilding mapalus, and community events mapalus. A qualitative research was done by focusing on a number of villages in Tombatu District in which the mapalus tradition still takes hold, namely the villages of Silian, Lobu, and Botelen. Several key informants were interviewed and repeated observations were made. The research results showed that: a) the reciprocal management system (taking turns or alternations) grows in the community independently and does not depend on any top-down program; b) the ethical value in reciprocal mapalus, namely Sitou Tumou Tou, is still maintained in the working ethos, organizational culture, and community participation; c) the compliance of members towards the mapalus ethical code was very high, where members were willing to be punished by whipping if they broke the code; d) mapalus has improved the economic condition of members and village residents through agriculture, house ownership, etc., and e) the reciprocal system in mapalus accelerates the spread of economic growth because of the system that was developed, namely the Community Economic Development. The conclusion is that the reciprocity in the mapalus is an economic empowerment model based on local wisdom that grew from the community in accordance with the philosophy of Sitou Tumou Timou Tou. Keywords: Reciprocal mapalus, empowerment